2011
DOI: 10.1161/atvbaha.111.227561
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Aortic Valve Disease in Mice Haploinsufficient for the Notch Pathway Effector RBPJK/CSL

Abstract: Objective— Calcific aortic valve disease is similar to atherosclerosis in that both diseases result from chronic inflammation and endothelial dysfunction. Heterozygous NOTCH1 mutations have been associated to calcific aortic disease and a bicuspid aortic valve. We investigated whether mice with genetic inactivation of the Notch signaling pathway are prone to develop valve disease when exposed to a predisposing diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 40 publications
1
68
0
3
Order By: Relevance
“…To confirm that the N12 allele is hypomorphic, we investigated whether haploinsufficient cardiac phenotypes associated with Notch1 (de la Pompa, 2009;de la Pompa and Epstein, 2012;Garg et al, 2005;Nus et al, 2011) +/12 and 39 were N1 +/+ ). By contrast, N1 12/12 embryos constituted ∼25% of the litters examined at E9.5, E14.5 and E18.5.…”
Section: Outbred N12 and N21 Homozygous Mice Display No Overt Phenotypementioning
confidence: 99%
“…To confirm that the N12 allele is hypomorphic, we investigated whether haploinsufficient cardiac phenotypes associated with Notch1 (de la Pompa, 2009;de la Pompa and Epstein, 2012;Garg et al, 2005;Nus et al, 2011) +/12 and 39 were N1 +/+ ). By contrast, N1 12/12 embryos constituted ∼25% of the litters examined at E9.5, E14.5 and E18.5.…”
Section: Outbred N12 and N21 Homozygous Mice Display No Overt Phenotypementioning
confidence: 99%
“…Transfection of Sox‐9 into VICs rescued the hypermineralising phenotype during Notch inhibition, suggesting that Notch signalling prevents mineralisation of the aortic valve in a Sox‐9‐dependent manner 59. Mice haploinsufficient for the Rbpjκ transcription factor and supplemented with a cholesterol‐rich diet and vitamin D develop CAVD but do not have BAV 60. Intriguingly, GATA5 ‐/‐ mice develop BAV (∼25% of littermates) and have lower expression of Jag1 and higher levels of mRNA encoding for Rbpjκ in embryonic tissues, suggesting dysregulation of the Notch pathway in these mice 61.…”
Section: Pathobiologymentioning
confidence: 99%
“…These studies demonstrated that loss of Notch signaling contributes to aortic valve calcification via a Sox9-dependent mechanism. Additional work by other investigators has supported these conclusions and have also demonstrated a role for Bmp2 as a downstream target of Notch1 signaling in this process and found that Notch1 haploinsufficient mice develop aortic valve calcification with aging [14,15].…”
Section: Notch1 Signaling and Aortic Valve Calcificationmentioning
confidence: 75%